2005
DOI: 10.1354/vp.42-6-797
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Features Associated withTritrichomonas foetus-induced Colitis in Domestic Cats

Abstract: Abstract. Tritrichomonas foetus is a venereal pathogen of naturally bred cattle. In domestic cats, T. foetus colonizes the colon, resulting in chronic, large-bowel diarrhea. The infection is prevalent among young, densely housed cats, and there is no effective treatment. To the authors' knowledge, the characteristic microscopic lesions of T. foetus infection in naturally infected cats have not been described. The aim of the study reported here was to characterize the histologic changes in the colon of seven ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 26 publications
1
63
0
Order By: Relevance
“…Using this approach, we demonstrated that T. foetus causes progressive cytotoxicity to the intestinal epithelium characterized by progressive loss of cells from the monolayer. An ongoing loss of colonic epithelial cells in vivo in cats naturally infected by T. foetus is supported by histological lesions that demonstrate attenuation of the surface epithelium in conjunction with cellular hyperplasia and hypertrophy and increased mitotic activity within the crypts (23).…”
Section: Discussionmentioning
confidence: 96%
“…Using this approach, we demonstrated that T. foetus causes progressive cytotoxicity to the intestinal epithelium characterized by progressive loss of cells from the monolayer. An ongoing loss of colonic epithelial cells in vivo in cats naturally infected by T. foetus is supported by histological lesions that demonstrate attenuation of the surface epithelium in conjunction with cellular hyperplasia and hypertrophy and increased mitotic activity within the crypts (23).…”
Section: Discussionmentioning
confidence: 96%
“…There is no convincing evidence that reproductive tract infection plays any role in the transmission of T. foetus in cats (Gray et al 2010). T. foetus affects mainly the colonic mucosa and the mucosa of the last part of the small intestine (Gookin et al 2001, Yaeger andGookin 2005).…”
Section: Pathogenesismentioning
confidence: 99%
“…These lesions, which were found to be more severe when associated with the presence of trichomonads, indicate ongoing loss of colonic epithelial cells. In severe cases, epithelial detachment and apoptosis result in loss of epithelial continuity and invasion of trichomonads into the subepithelium38 (Fig 6). Interestingly, similar subepithelial invasion of trichomonads has been described in the intestinal tract of fetuses aborted from cows infected with bovine T. foetus 81…”
Section: Pathogenesis Of Trichomonosismentioning
confidence: 99%
“…38 The proinflammatory molecules responsible for eliciting intestinal inflammation in T. foetus infection are unknown. Immunohistochemical examination of colonic mucosa from naturally infected cats not only shows T. foetus organisms in contact with the surface epithelium but also the presence of immunoreactive T. foetus antigen within the epithelial cells and lamina propria 10, 38. Therefore, release of proinflammatory cytokines by the infected intestinal epithelial cells is suspected, but not yet conclusively identified.…”
Section: Pathogenesis Of Trichomonosismentioning
confidence: 99%